Avaliação do efeito da bebida de açaí no perfil lipídico e glicêmico em ratos Wistar - Fernando, Francine da Silva e Lima de (Universidade Federal de São Carlos, 2013)
The Chronic Noncommunicable Diseases are a major global public health challenges , and are determined mostly by the association of modifiable risk factors , such as nutrition . It is believed that the use of functional foods with antioxidant properties can positively affect the incidence of such diseases. Given this context highlights the Acai ( Euterpe oleracea ) , which features in its pulp components with the ability to inhibit or reduce oxidation processes generated by free radicals in the body . Thus , this study aimed to evaluate the effect of the consumption of the drink acai in glucose and lipid profile of Wistar rats . For forty- five days 12 Munich- Wistar rats ( Rattus norvegicus ) adult females with an average weight of 250g were divided into two groups ( Acai and Control ) received water and feed ad libitum to except the group that had the Acai replaced by drinking water Acai . At the end of the experiment the animals were anesthetized and euthanized . Blood samples were collected for analysis of biochemical parameters (glucose , cholesterol , triglycerides and blood count ) and tissue samples for histological analyzes . In the analyzed variables , even without showing statistically significant differences , descriptive results showed the maintenance of body weight and glucose and lipid reduction , and increase in some blood components relevant group Acai . Thus Because the population growing interest in consuming food which prevent diseases , promote health and improve the quality of life, it is suggested that new experimental models are implemented so that the beneficial effects are enjoyed arising from the consumption of açaí.
Keywords: Biotecnologia; Açaí; Doenças crônicas; Glicemia; Dislipidemias; Ratos Wistar; Wistar rats; Chronic disease; Glycemia; Dyslipidemia; OUTROS